(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Political revolutions are transformative events that reshape societies and states. This paper examines the concept of political revolutions, classifying them based on their objectives, methods, and scope. It explores the diverse range of factors that trigger such upheavals, from socioeconomic inequalities to authoritarian rule and ideological clashes. Through comparative analysis of key revolutions, such as those in France, U.S.A, Russia, Uzbekistan, and Iraq, this essay highlights the complex legacies and long-term impacts of revolutions, emphasizing their significance as catalysts for political, social, and economic change.